Implementation of Pancasila Values Through Drawing Batik Motifs to Form a Character of Love for the Homeland in Children Aged 5-6 Years at the NU Muslimat Kindergarten, West Waru - Syarif Hidayatullah; Mediyana; Dewi Pusparini (STIT Attaqwa, 2025)
This study aims to examine the implementation of Pancasila values in shaping the character of love for the country through batik motif drawing activities for children aged 5-6 years at Muslimat NU Kindergarten. The main focus of this research includes: (1) how is the process of implementing Pancasila values in shaping the character of love for the country through batik motif drawing activities, (2) what are the obstacles faced by teachers and students in the process, and (3) how do teachers overcome these obstacles. This research uses a descriptive qualitative approach with a case study method. Data collection techniques were conducted through observation, interviews, and documentation. The results showed that the process of implementing Pancasila values was carried out through thematic learning planning, introduction of local and national culture in the form of batik, strengthening the values of love for the country through activities illustrating the cultivation of Pancasila values. The obstacles faced include the low level of understanding of children, limited learning time, lack of resources and differences in children's ability levels. Teachers overcome these obstacles by using visual media and stories, learning with play and singing methods, personal approach, collaboration with parents and periodic reflection and evaluation. The conclusion of this study is that the activity of drawing batik motifs can be an effective medium in instilling Pancasila values, especially love for the country, in early childhood if supported by appropriate learning strategies.